Living on the Margins: Secluded Characters in Southern Literature - Gourdoux, Eva (Margins/Marges/Margini, 2025)
The South of the United States has often been looked at as a marginal region by historians and literary critics alike. The works of white Southern authors like William Faulkner (1897-1962), Flannery O’Connor (1925-1965) and Eudora Welty (1909-2001) have been associated with this so-called marginality, despite the writers’ efforts to keep clear from this inescapable reputation. More often than not, the unwanted marginality pervades the novels and short stories of these authors: misfits, disabled and reclusive characters people their stories. In some of their works, Faulkner, O’Connor and Welty depict characters who defy the norm, whether it be through their bodies or their actions. The secluded way of life of these characters tends to amplify their abnormality and anchors them deeper into the margins of their homes, in the recesses of Mississippi, in the Georgia countryside or on the outskirts of the fictional land of Yoknapatawpha. This study seeks to analyze the marginality of reclusive characters in white Southern literature – more precisely in selected works by Faulkner, O’Connor and Welty – and underlines the liminal aspect of margins. The first part of this article focuses on the depiction of abnormality in these works: whether they challenge the social norms or even the bodily norms by way of grotesque traits, the authors’ secluded characters embody the margin. The last part demonstrates the paradoxical realistic power of the margins, as they allow for the surprising representation of unamable taboos. The secluded characters of the works under study are marginal figures in a seemingly marginal world, but actually use marginality to cross boundaries.